Role of Capacity/Skill Development Trainings in Rural Livelihood: A Case Study of Hapur, Dang - Pasa, Rajan Binayek (Journal of Training and Development, 2017)
Education has transformative potential if it is connected to people’s life and their livelihood. And education has been seen as a means of developing capabilities, promoting employment potentials, and reducing poverty in rural communities. Reflecting upon those ideas, this study explained transformative role of capacity/skill development training on livelihood in rural contexts. There is no doubt, capable, knowledgeable and skillful youths have been playing change agent role especially in local levels. The study applied quantitative case study research methodology to test the significant relationship between study variables. Questionnaires, and key informant interview techniques were applied while collecting data information. Set of questionnaires were filled up with 108 respondents selected by using stratified random sampling methods. The study found significant role of capacity/skill development trainings on rural livelihoods. Further, skilled and capable youths are becoming human capital in the society and working for transforming social capital. They are also generating household economy by involving in income generate activities. The study concluded that capacity/skill development training program conducting in local level help to nourish knowledge, ability and develop vocational skills of male and female youths. And they are now playing transformative role in the society and achieving rural prosperity. Therefore, findings of the study can become fruitful guidelines to the policy makers and planners in local levels.